E-Government in Selangor: a Case Study of Citizen’s Participation and its Challenges - Nazreena Mohammed Yasin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
In the study of democracy, E-Government is significant as it functions as a platform to promote e-democracy by promoting people's participation through utilising modern technology such as the Internet. However, it is noted that most of the local government websites are still stagnant and lacking in criteria and features of embracing two-ways communication. This can hinder the process to promote e-democracy in the local government websites. This study uses Marianne Kneuer's framework to examine the impact of e-government on e-democracy in Selangor by using content analysis method. The objectives of this research are to study the progress of e-democracy implementation in the local government websites in Selangor by looking at the features based on the framework proposed by exploring three categories: free and equal access, e-participation, and e-governance. There are four local government websites selected in this study, namely Petaling Jaya, Subang Jaya, Kajang, and Klang local government websites. Although it is noted that the local governments have provided some features related to e-democracy, the features need to be updated and improved from time to time. The challenges to the effectiveness and efficiency of e-government and e-democracy were also highlighted based on the results collected and interviews conducted with the website administrators. Those were namely allocation of budget, feature standardization, regular updates of the websites, unclear division of task, leader’s approach and also public awareness and acceptance. The e-democracy implementation in local government websites has been accepted positively by the local government administrator by improving their websites which are in line with e-democracy features.